A prospective surveillance study to determine the prevalence of 16S rRNA methyltransferase-producing Gram-negative bacteria in the UK. (18th June 2021) - Taylor, Emma; Bal, Abhijit M.; Balakrishnan, Indran; Brown, Nicholas M.; Burns, Phillipa; Clark, Marilyn; Diggle, Mathew; Donaldson, Hugo; Eltringham, Ian; Folb, Jonathan; Gadsby, Naomi; Macleod, Mairi; et al.
Abstract: Objectives: To determine the prevalence of 16S rRNA methyltransferase- (16S RMTase-) producing Gram-negative bacteria in patients in the UK and to identify potential risk factors for their acquisition. Methods: A 6 month prospective surveillance study was conducted from 1 May to 31 October 2016, wherein 14 hospital laboratories submitted Acinetobacter baumannii, Enterobacterales and Pseudomonas aeruginosa isolates that displayed high-level amikacin resistance according to their testing methods, e.g. no zone of inhibition with amikacin discs. Isolates were linked to patient travel history, medical care abroad, and previous antibiotic exposure using a surveillance questionnaire. In the reference laboratory, isolates confirmed to grow on Mueller-Hinton agar supplemented with 256 mg/L amikacin were screened by PCR for 16S RMTase genes armA, rmtA – rmtH and npmA, and carbapenemase genes ( bla KPC, bla NDM, bla OXA-48-like and bla VIM ). STs and total antibiotic resistance gene complement were determined via WGS. Prevalence was determined using denominators for each bacterial species provided by participating hospital laboratories. Results: Eighty-four isolates (44.7%), among 188 submitted isolates, exhibited high-level amikacin resistance (MIC >256 mg/L), and 79 (94.0%) of these harboured 16S RMTase genes. armA (54.4%, 43/79) was the most common, followed by rmtB (17.7%, 14/79), rmtF (13.9%, 11/79), rmtC (12.7%, 10/79) and armA + rmtF (1.3%, 1/79). The overall period prevalence of 16S RMTase-producing Gram-negative bacteria was 0.1% (79/71 063). Potential risk factors identified through multivariate statistical analysis included being male and polymyxin use. Conclusions: The UK prevalence of 16S RMTase-producing Gram-negative bacteria is low, but continued surveillance is needed to monitor their spread and inform intervention strategies.